2018
DOI: 10.1093/fampra/cmy064
|View full text |Cite
|
Sign up to set email alerts
|

Patients on levothyroxine replacement in the community: association between hypothyroidism symptoms, co-morbidities and their quality of life

Abstract: In Asian patients with hypothyroidism, weight gain, feeling tired, feeling weak, having dry or coarse skin, leg swelling and increased number of co-morbidities and symptoms were significantly associated with poorer QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Patients taking desiccated thyroid extract (DTE) reported a higher median treatment satisfaction of 7 (IQR, 5-9) compared to other treatments. Patients receiving LT4 treatment reported a lower satisfaction score of 5 (IQR 3-7), while those receiving LT4 + LT3 reported a higher satisfaction score of 6 (IQR, [3][4][5][6][7][8]. Patients taking DTE were less likely to report problems related to weight management, fatigue/energy levels, mood, and memory compared to patients taking other agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients taking desiccated thyroid extract (DTE) reported a higher median treatment satisfaction of 7 (IQR, 5-9) compared to other treatments. Patients receiving LT4 treatment reported a lower satisfaction score of 5 (IQR 3-7), while those receiving LT4 + LT3 reported a higher satisfaction score of 6 (IQR, [3][4][5][6][7][8]. Patients taking DTE were less likely to report problems related to weight management, fatigue/energy levels, mood, and memory compared to patients taking other agents.…”
Section: Discussionmentioning
confidence: 99%
“…5 Furthermore, Tan and colleagues evaluated Asian patients receiving levothyroxine replacement therapy in the community setting and found that a decreased quality of life (QOL) score was associated with hypothyroid patients with a single persistent symptom, including weight gain (adjusted OR [95% CI], 3.12 [1.71-5.68]), feeling weak (2.12 [1.09-4.11], and having dry or coarse skin (2.27 [1.24-4.14]), but decreased QOL was not associated with TSH or free thyroxine levels. 8 Thyroid related symptoms may be subtle and challenging to quantify yet serial measures of such symptoms in patients do support the utility of this approach to patient care. 2,9-13 A previously reported ten Symptom Scale Instrument (Hypothyroid Symptom Scale, HSS) has shown its ability to quantify persistent symptoms in levothyroxine treated patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Body weight is probably the most widely recognized proxy for thyroid hormone action, even if the association between weight gain and hypothyroidism is at best tenuous. Importantly, weight gain is one of the most important drivers of dissatisfaction among patients affected by hypothyroidism ( 3 , 4 , 17 , 45 , 48 ) and conversely, weight loss was the greatest reason to declare satisfaction with the treatments among patients who preferred combination therapy or DTE on clinical trials ( 9 , 10 , 18 , 22 , 25 ). Moreover, a crossover study indicated that therapy with LT3 alone was associated with significant weight loss ( 49 ).…”
Section: Endpointsmentioning
confidence: 99%
“…Thyroid autoimmunity per se may also lead to symptoms through chronic inflammation, 16,17 though not all studies have confirmed this 18 . At least four possible hypotheses may explain persistent symptoms and dissatisfaction with treatment in patients with hypothyroidism who appear to be adequately replaced with L‐T4 on biochemical grounds: lack of efficacy of L‐T4 in restoring euthyroidism at tissue level 11,15 ; autoimmunity, rather than hypothyroidism being the culprit 16,17 ; pre‐existing non‐thyroidal morbidity and/or post‐thyroid diagnosis comorbidities 19‐23 ; negative experiences with healthcare professionals and other psychosocial factors unrelated to hypothyroidism being the cause of persistent symptoms 1 …”
Section: Introductionmentioning
confidence: 99%